Optimalisasi Penggunaan Fly Ash Untuk Reduksi Kadar Besi (Fe) Dan Mangan (Mn) Serta Peningkatan pH Dalam Air Asam Tambang - Rofi Taufiqurrahman; Shalaho Dina Devy; Windhu Nugroho; Agus Winarno; Henny Magdalena (Manufaktur: Publikasi Sub Rumpun Ilmu Keteknikan Industri, 2024)
Coal mining activities often result in acid mine drainage (AMD), which can cause environmental pollution if not properly managed. This study aims to evaluate the potential use of fly ash from the Stream Power Plant (PLTU) Tenggarong to mitigate the impacts of AMD, specifically targeting iron (Fe), manganese (Mn), and pH parameters. Acid Mine drainage is formed when sulfide minerals oxidize, producing acidic compounds that can harm the environment. This research focuses on analyzing the ability of fly ash to adsorb iron and manganese from AMD solutions, as well its capability to increase solution pH. Based on the conducted research, the optimum pH value was achieved when using 10 grams and 15 grams of fly ash in the adsorption process. The optimum concentration of iron (Fe) was attained using 10 grams to 15 grams of fly ash, while for manganese (Mn), it was achieved with 20 grams to 25 grams of fly ash. The adsorption process using 25 grams of fly ash showed the highest efficiency in reducing iron (Fe) concentration by 93.78 % and manganese (Mn) concentration by 75.47 %.